Effect of Transglutaminase on the Quality Properties of Chicken Breast Patties - Uran, Harun; Aksu, Filiz; Yilmaz, Ismail; Durak, M. Zeki (KAFKAS UNIV, VETERINER FAKULTESI DERGISI, 2013)
Transglutaminase enzyme is known to improve the textural and several other quality properties of food. In this study, patties were produced from chicken breast and dividend into three groups. The first group was not treated by transglutaminase and called as control samples. The second and third group patty samples were treated by 0.5% and 1% transglutaminase, respestively. Physical, chemical and sensory properties of the control and transglutaminase treated patty samples were studied. The transglutaminase treatment did not significantly affect the ash, lipid, protein content, colour properties (L, a, b values) and sensory properties of chicken breast patties compared to the control samples (P>0.05). However, dry matter content of the 1% enzyme treated samples was significantly (P<0.05) higher than the control and 0.5% transglutaminase treated samples. On the other hand, the pH of enzyme treated patties was found to be lower than the control samples. In addition, the transglutaminase treatments were significantly (P<0.05) effective in reducing the cooking loss and significantly improved the textural properties of the chicken breast patties (P<0.01).
Keywords: Transglutaminase; Chicken breast patty; Quality; MICROBIAL TRANSGLUTAMINASE; BINDING; Veterinary Sciences